Influence of plasma shaping effect on peeling-ballooning instability. (28th September 2021) - Qin, Chenchen; Mou, Maolin; Chen, Shaoyong; Tang, Changjian
Abstract: The influence of plasma shaping effect on peeling-ballooning mode is studied linearly and nonlinearly using the three-field module of BOUT++. Without considering the variations of pressure pedestal and bootstrap current induced by shaping, our simulations demonstrate that shaping effect on magnetic surfaces also influences peeling-ballooning instability significantly. The shape of growth rate spectrum tends to shift to a lower toroidal mode number ( n ) with the increase of elongation ( κ ), and the growth rates become smaller for all n modes with the increase of triangularity ( δ ) in the linear simulation. Further analysis demonstrates that peeling-ballooning mode is stabilized mainly by the increased magnetic shear ( s ) for elongation and the decreased normalized pressure gradient ( α ) for triangularity. In the nonlinear simulation, the elongation can lead to a larger pedestal collapse while the triangularity plays an opposing role. That is because the dominance of low n mode that arises with the increase of κ and decrease of δ, can lead to a larger energy loss. The results indicate that the effect of triangularity on the magnetic surface is quite important since it leads to ELM mitigation without any variations of pressure pedetal and bootstrap current, which provide an innovative mechanism to explain the ELM mitigation phenomenon due to plasma shaping.